(untitled) (Advancements in Homeopathic Research, 2024)
Anemia is a common hematological disorder globally, often managed with conventional iron supplements that may lead to gastrointestinal side effects and poor compliance. Homeopathy, offering a holistic approach, aims to support the body’s innate healing mechanism and address the underlying causes of anemia. This study investigates the safety and efficacy of homeopathic formulation Willfort™ Anemia Drops in mitigating adenine-induced Anemia in male Sprague Dawley rats, revealing encouraging results. Before this investigation, multiple formulations were developed in accordance with the internal product development protocol. Based on expert reviews, laboratory compatibility trials, and stability studies, two variants (AD-002/A-20-5 and AD-003/A-20-6) were selected for this study.